Biotechnology organizations in action : turning knowledge into business - Norus, Jesper; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 2002)
This volume analyzes the dynamics and interactive processes among the players (individuals, institutions, and organizations/firms) that have constituted and legitimized the development of the biotechnology industries. The unit of analysis is small entrepreneurial firms developing biotechnological products and processes. What types of strategies are small entrepreneurs pursuing in order to create markets for their new products and processes, and how have specific strategies emerged? The primary interest is the network process through which the technological field and the development of institutions and routines evolve and co-evolve. The theoretical contribution of the book is its focus on the development of the concept of networks. From being regarded as a relative static concept the book transforms the concept into a dynamic concept of networking. The dynamic view on the creation and development of new technologies through network formations is linked to the concept of strategy that is used throughout the book. Hence the strategies are developed along with the creation of technological knowledge, and it is hoped that the diffusion of this specific knowledge will bring new actors into the technological arena or community. This book will be useful to the academic community, those studying the formation of networks, strategic management, organizational behavior, and management of technology, as well as business observers with a specific interest in the evolution of the biotechnology industry.
Chapter 1. Regulation of cellulose biosynthesis in developing xylem -- Chapter 2. Xylem formation and lignification in trees and model species -- Chapter 3. Spatial and temporal regulation of lignification during tracheary element differentiation -- Chapter 4. Final and fatal step of tracheary element differentiation -- Chapter 5. Arabidopsis as a model for investigating gene activity and function in vascular tissues -- Chapter 6. Molecular mechanisms of vascular pattern formation -- Chapter 7. The asymmetric leaves2 (AS2) gene of arabidopsis thaliana regulates lamina formation and is required for patterning of leaf venation -- Chapter 8. Biosynthesis of cellulose -- Chapter 9. Functional analysis of polysaccharide synthases responsible for cell wall synthesis in higher plants -- Chapter 10. Analysis of secondary cell wall formation in arabidopsis -- Chapter 11. Organization of cellulose-synthesizing terminal complexes -- Chapter 12. Regulation of dynamic changes in cell wall polysaccharides -- Chapter 13. Microfibrils build architecture: A geometrical model -- Chapter 14. Occurrence of high crystalline cellulose in the most primitive tunicate, appendicularian -- Chapter 15. The role of cortical microtubules in wood formation -- Chapter 16. Xylan and lignin deposition on the secondary wall of fagus crenata fibers -- Chapter 17. Isolation of monoclonal antibodies recognizing xylem cell wall components by using a phage display subtraction method -- Chapter 18. On the mechanism to regulate the ratio of syringyl to guaiacyl moieties in lignin -- Chapter 19. The behavior of exogenous sinapic acid in the differentiating xylem of angiosperm -- Chapter 20. Functional analysis of phenylalanine ammonia-lyase gene promoter of popular -- Chapter 21. Xylem peroxidases: Purification and altered expression -- Chapter 22. Immunolocalization of enzymes involved in lignification -- Chapter 23. Lignin biosynthesis in poplar: Genetic engineering and effects on kraft pulping -- Chapter 24. Analysis of transgenic poplar in which the expression of peroxidase gene is suppressed -- Chapter 25. Transcriptional regulation of lignin biosynthesis by tobacco lim protein in transgenic woody plant -- Chapter 26. Genetic engineering of pinus radiata and picea abies, production of transgenic plants and gene expression studies -- Chapter 27. Analysis of wood development with a genomic approach: Eucalyptus ESTs and TAC genomic library -- Chapter 28. Modifying populus environmental responses: Impacts on wood quantity and quality -- Chapter 29. Two insect-resistant genes were transferred into poplar hybrid and transgenic poplar shew insect-resistance -- Chapter 30. Modification of flowering in transgenic trees -- Chapter 31. Possible approaches for studying three dimensional structure of lignin -- Chapter 32. Involvement of peroxidase and hydrogen peroxide in the metabolism of b-thujaplicin in fungal elicitor-treated cupressus lusitanica suspension cultures -- Chapter 33. A factor controlling b-thujaplicin production in suspension culture of cupressus lusitanica -- Chapter 34. Endogenous plant hormones in protoplasts of embryogenic cells of conifers -- Chapter 35. Efficient plant regeneration of larix kaempferi -- Chapter 36. Somatic embryogenesis of Japanese conifers -- Chapter 37. Application of somatic embryogenesis to tree improvement in conifers -- Chapter 38. Somatic embryogenesis and plantlet regeneration in pinus armandii var. amamiana -- Chapter 39. Plant regeneration from somatic embryos in pinus thunbergii (Japanese black pine) and pinus densiflora (Japanese red pine) -- Chapter 40. Concepts and background of photoautotrophic micropropagation -- Chapter 41. Photoautotrophic micropropagation of tropical and subtropical woody plants -- Chapter 42. Large-scale photoautotrophic micropropagation in a scaled-up vessel -- Chapter 43. Mass-propagation of coffee from photoautotrophic somatic embryos -- Chapter 44. Automation in somatic embryo production -- Chapter 45. A closed-type transplant production system -- Chapter 46. Photoautotrophic micropropagation of rhododendron.
Includes bibliographical references (pages 223-232).
Print version record.
Elsevier
Keywords: Biotechnology industries; BUSINESS & ECONOMICS -- Industries -- Service; Biotechnology industries; Biomedical Technology; Commerce; Electronic books